Pengaruh Profitabilitas, Likuiditas, Struktur Aktiva Terhadap Struktur Modal Melalui Kebijakan Dividen Pada Perusahaan Makanan Dan Minuman Di BEI - Zuhri, Haszaghi Ramadhan; Susyanti, Jeni; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the Profitability variable (ROA), Liquidity variable (DAR), Asset Structure variable on Capital Structure through the Dividend Policy variable (DPR). The sampling technique was carried out using the Purposive Sampling technique, so that the sample obtained was 10 food and beverage companies listed on the Indonesia Stock Exchange for the 2019 - 2022 period with a total of 40 observation data over 4 years of observation. The data collection technique used is documentation with data sources using secondary data taken through the official website of the Indonesian Stock Exchange. This research uses the path method (Path Analysis) with SPSS 26 software tools. The results of this research show that: profitability has a negative effect on capital structure, liquidity has a positive effect on capital structure, while asset structure and dividend policy have a negative effect on capital structure but not significant. Furthermore, profitability indirectly through dividend policy has a significant influence on capital structure, while liquidity indirectly through dividend policy does not have a significant influence on capital structure, and asset structure indirectly through dividend policy has a significant influence on capital structure. Keywords: Profitability, Liquidity, Asset, Dividend Policy, Capital